Pro-differentiating and radiosensitizing effects of inhibiting HDACs by PXD-101 (Belinostat) in in vitro and in vivo models of human rhabdomyosarcoma cell lines. (1st October 2019) - Marampon, Francesco; Di Nisio, Valentina; Pietrantoni, Ilaria; Petragnano, Francesco; Fasciani, Irene; Scicchitano, Bianca Maria; Ciccarelli, Carmela; Gravina, Giovanni Luca; Festuccia, Claudio; Del Fattore, Andrea; Tombolini, Mario; De Felice, Francesca; et al.
Abstract: This study describes the in vitro and in vivo activity of PXD-101 (Belinostat), a novel hydroxamic acid-type pan-HDACs inhibitor characterized by a larger safety and efficacy, on myogenic-derived PAX3/FOXO1 fusion protein positive (RH30) or negative (RD) expressing rhabdomyosarcoma (RMS) cell lines. PXD-101 at low doses efficiently inhibited HDACs activity and counteracted the transformed phenotype of RMS by inducing growth arrest and apoptosis, affecting cancer stem cells population and inducing differentiation in RD. Notably, PXD-101 induced oxidative stress promoting DNA damages and affected the ability of RMS to assemble mitotic spindle. PXD-101 radiosensitized by inducing G2 cell cycle growth arrest, enhancing the radiation's ability to induce ROS accumulation and compromising both the ability of RMS to detoxify from ROS and to repair DNA damage. PXD-101 transcriptionally and post-transcriptionally affected c-Myc expression, key master regulator of rhabdomyosarcomagenesis and RMS radioresistance. All in vitro data were corroborated by in vivo experiments showing the cytostatic effects of PXD-101 when used alone and at low dose and its ability to promote the RT-induced killing of RMS. Taken together, our data confirm that altered HDACs activity plays a key role in RMS genesis and suggest PXD-101 as a valid therapeutic strategy particularly in combination with RT. Highlights: PXD-101 exhibited significant anti-rhabdomyosarcoma activity. PXD-101 affected stemness, induces differentiation and concomitant cell death. PXD-101 induced oxidative stress and DNA damage. PXD-101 interferes with the mitotic spindle assembly.